2023
DOI: 10.1021/acs.jpcc.3c02379
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Reactivity of the Na3PS4 Solid-State Electrolyte with the Sodium Metal Negative Electrode Using Total Trajectory Analysis with Neural-Network Potential Molecular Dynamics

Abstract: Rechargeable batteries play a central role in the global shift from fossil fuels to renewable energy. Since the commercial introduction of lithium-ion batteries in the early 1990s, recent progress is focused on the development of solid-state materials and new battery chemistries. Specifically, solid-state sodium ion batteries are an attractive alternative alongside lithium-based rechargeable batteries, with improvements in safety, lifespan, sustainability, and price. Critical to the battery performance are ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…We confirmed no marked difference between both compounds, so that slow Na diffusivity is not a primary reason for the suppression of decomposition reaction in Na 3 PS 3 O. For sulfur, there was a sequential breakdown of P−S bonds as reported in our previous study [39] . For oxygen, the P−O bond was found to be very stable, with a very limited number of decomposition reactions of the neighboring P−S bonds.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…We confirmed no marked difference between both compounds, so that slow Na diffusivity is not a primary reason for the suppression of decomposition reaction in Na 3 PS 3 O. For sulfur, there was a sequential breakdown of P−S bonds as reported in our previous study [39] . For oxygen, the P−O bond was found to be very stable, with a very limited number of decomposition reactions of the neighboring P−S bonds.…”
Section: Resultssupporting
confidence: 87%
“…The platinum electrode was used due to issues with sodium metal obscuring the band gap as explained in our previous study. [39] Cross-sectional DOS plots with the sodium metal electrode are shown in Figure S27. In both Figure 6c and Figure 6d (zoomed to the Fermi level), it can be observed that from oxygen towards tellurium the band gap decreases, indicating a greater reactivity towards tellurium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations